2019
DOI: 10.5811/westjem.2019.7.41661
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Gateway Effects on Adolescent Substance Use

Abstract: Given the rise in teenage use of electronic nicotine delivery systems ("vaping") in congruence with the increasing numbers of drug-related emergencies, it is critical to expand the knowledge of the physical and behavioral risks associated with developmental nicotine exposure. A further understanding of the molecular and neurochemical underpinnings of nicotine's gateway effects allows emergency clinicians to advise patients and families and adjust treatment accordingly, which may minimize the use of tobacco, ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
66
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 164 publications
(202 reference statements)
0
66
0
1
Order By: Relevance
“…If e-cigarettes are being used in settings where smoking is prohibited, this may increase cumulative nicotine exposure and the associated adverse effects. It is possible that dual-use may represent a transition to tobacco product use, a process known as the gateway effect, and longitudinal evidence for this effect is mounting [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…If e-cigarettes are being used in settings where smoking is prohibited, this may increase cumulative nicotine exposure and the associated adverse effects. It is possible that dual-use may represent a transition to tobacco product use, a process known as the gateway effect, and longitudinal evidence for this effect is mounting [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another common health-risk behavior is substance use, which includes cigarette smoking, alcohol consumption, and other forms of illicit drug use (e.g., cannabis, ecstasy, cocaine). Several studies ( Radliff et al, 2012 ; Durand et al, 2013 ) indicated that substance use normally begins in adolescence, with cigarette smoking and alcohol consumption as the gateway to other forms of illicit drug use in subsequent years ( Ren and Lotfipour, 2019 ). The Health Behavior in School-aged Children study on substance use ( Inchley et al, 2020 ) reported a prevalence of alcohol consumption of 20% in boys and 18% in girls and a prevalence of cigarette smoking of 7% in both genders, when assessed for the last 30 days.…”
Section: Introductionmentioning
confidence: 99%
“… 15 16 A major concern regarding e-cigarettes is that they also seem to appeal to non-smoking teenagers 17 18 and might serve as a gateway to initiation of tobacco smoking as well as other drugs. 11 17 19 However, another explanation for the association between e-cigarette use and tobacco smoking may be that these behaviours share many risk factors such as social disadvantage, addictive behaviours, low academic achievement, and having family members or friends that smoke. 20–24 These shared characteristics may serve as a common liability for any tobacco or nicotine product, 25 26 which implies that the sequential order of product initiation is of less importance.…”
Section: Introductionmentioning
confidence: 99%